2017
DOI: 10.3389/fnhum.2017.00085
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Effects to a Multimodal Dual-Task after Working Memory Training and Associated Neural Correlates in Older Adults – A Pilot Study

Abstract: Working memory (WM) performance declines with age. However, several studies have shown that WM training may lead to performance increases not only in the trained task, but also in untrained cognitive transfer tasks. It has been suggested that transfer effects occur if training task and transfer task share specific processing components that are supposedly processed in the same brain areas. In the current study, we investigated whether single-task WM training and training-related alterations in neural activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 98 publications
2
26
0
2
Order By: Relevance
“…Other than the presented interaction effects of age and emotions, caffeine, and hormones, other studies looked at working memory training in the older population in order to investigate working memory malleability in the aging brain. Findings of improved performance for the same working memory task after training were consistent across studies ( Dahlin et al, 2008 ; Borella et al, 2017 ; Guye and von Bastian, 2017 ; Heinzel et al, 2017 ). Such positive results demonstrated effective training gains regardless of age difference that could even be maintained until 18 months later ( Dahlin et al, 2008 ) even though the transfer effects of such training to other working memory tasks need to be further elucidated as strong evidence of transfer with medium to large effect size is lacking ( Dahlin et al, 2008 ; Guye and von Bastian, 2017 ; Heinzel et al, 2017 ; see also Karbach and Verhaeghen, 2014 ).…”
Section: Age and Working Memorysupporting
confidence: 72%
“…Other than the presented interaction effects of age and emotions, caffeine, and hormones, other studies looked at working memory training in the older population in order to investigate working memory malleability in the aging brain. Findings of improved performance for the same working memory task after training were consistent across studies ( Dahlin et al, 2008 ; Borella et al, 2017 ; Guye and von Bastian, 2017 ; Heinzel et al, 2017 ). Such positive results demonstrated effective training gains regardless of age difference that could even be maintained until 18 months later ( Dahlin et al, 2008 ) even though the transfer effects of such training to other working memory tasks need to be further elucidated as strong evidence of transfer with medium to large effect size is lacking ( Dahlin et al, 2008 ; Guye and von Bastian, 2017 ; Heinzel et al, 2017 ; see also Karbach and Verhaeghen, 2014 ).…”
Section: Age and Working Memorysupporting
confidence: 72%
“…This again enables participants to allocate more attention to concurrent tasks, resulting in better performance in this task. Also, during working memory tasks, an increase in fronto-parietal neural activation with increasing cognitive load has been described in terms of an adaptive mechanism in younger adults ( Nagel et al, 2011 ; Heinzel et al, 2014 ; Heinzel et al, 2017 ). Accordingly, our findings further contribute to the idea that individuals who vary in their cognitive abilities might compensate for this by investing greater effort.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive training was developed to improve different cognitive functions such as attention, perception, and memory in young and older adults (Heinzel, Rimpel, Stelzel, & Rapp, ; Loosli et al, ; Mahncke, Bronstone, & Merzenich, ; Salminen, Kühn, Frensch, & Schubert, ), and to tap into the aging brain's plasticity to improve cognitive functions such as intelligence, episodic memory, WM, and executive functions (Dahlin, Nyberg, Bäckman, & Neely, ; Lawlor‐Savage & Goghari, ; Yang et al, ). Moreover, WM training has been shown to yield beneficial effects in older adults reducing age‐related WM decline (Borella, Carretti, Riboldi, & De Beni, ; Borella, Carretti, Zanoni, Zavagnin, & De Beni, ; Brehmer, Westerberg, & Bäckman, ; Buschkuehl, Jaeggi, & Jonides, ; Li et al, ; Schmiedek, Lövdén, & Lindenberger, ), albeit that only a few cognitive training studies, in terms of N ‐back training, have shown positive effects across age (Heinzel et al, ; Lawlor‐Savage & Goghari, ; Loosli et al, ). Following a series of studies, Dahlin, Neely, Larsson, Bäckman, and Nyberg (), Dahlin, Nyberg, et al () and Li et al () reported that training on an N ‐back task improves WM of both young and older healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…, albeit that only a few cognitive training studies, in terms of N-back training, have shown positive effects across age (Heinzel et al, 2017;Lawlor-Savage & Goghari, 2016;Loosli et al, 2016). Following a series of studies, Dahlin, Neely, Larsson, Bäckman, and Nyberg (2008), and Li et al (2008) reported that training on an N-back task improves WM of both young and older healthy subjects.…”
mentioning
confidence: 99%